(untitled) (Polifonia, 2013)
O presente texto foi apresentado por ocasião da comemoração de dez anos de criação do Mestrado em Estudos de Linguagem (MeEL), na UFMT. Nele, a autora se dobra sobre o acontecimento da Linguística em sua vida pessoal, acadêmica e profissional, rememorando desde o primeiro encontro com a disciplina até sua participação na criação e efetivação do Programa. ABSTRACT: The present text was presented at the commemoration of ten years of the Masters Program in Language Studies (MeEL) at UFMT. In it, the author reflects over the happening of Linguistics in her personal, academic and professional life, recollecting from the first encounter with the discipline to her participation in the creation and realization of the Program.